2016
DOI: 10.1007/s00394-016-1329-3
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of milk and vegetable lipids in infant formula changes gut digestion, mucosal immunity and microbiota composition in neonatal piglets

Abstract: The incorporation of both milk fat and MFGM fragments in infant formula modifies protein digestion, the dynamic of the immune system maturation and the faecal microbiota composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 49 publications
2
36
0
5
Order By: Relevance
“…211 The addition of MFGM alone did not lead to changes in gut microbiota composition in 28-day-old piglets compared with standard IFs but the addition of both dairy lipids and MFGM affected gut microbiota composition, with an increase in Proteobacteria and a decrease in Firmicutes phyla compared with piglets fed a standard vegetable-oil IF. 212 These changes were similar to those observed at 3 months of age between breastfed infants and infants fed a vegetable-oil-based IF. 213 To conclude, relationships have been described between macronutrients and specific bacteria but further studies are needed to better understand them and evaluate their long-term impact on health.…”
Section: Effects Of the If Composition On Gut Microbiota: A Possible supporting
confidence: 76%
“…211 The addition of MFGM alone did not lead to changes in gut microbiota composition in 28-day-old piglets compared with standard IFs but the addition of both dairy lipids and MFGM affected gut microbiota composition, with an increase in Proteobacteria and a decrease in Firmicutes phyla compared with piglets fed a standard vegetable-oil IF. 212 These changes were similar to those observed at 3 months of age between breastfed infants and infants fed a vegetable-oil-based IF. 213 To conclude, relationships have been described between macronutrients and specific bacteria but further studies are needed to better understand them and evaluate their long-term impact on health.…”
Section: Effects Of the If Composition On Gut Microbiota: A Possible supporting
confidence: 76%
“…But MFGM-supplementation did not change FITC-dextran intestinal permeability, although it improved expression of tight junction proteins. Using neonatal piglets, we also evidenced MFGM-induced mucosal growth without any impact on epithelial permeability as measured in Ussing chambers (Le Huërou-Luron et al, 2018). Moreover, in challenging conditions against pathogenic bacteria such as Clostridium difficile or Listeria monocytogenes, MFGM were described as conferring protection, probably by stimulating mucin secretion and preventing adherence of pathogens to the intestinal mucosa in rats (Sprong et al, 2012;Bhinder et al, 2017).…”
Section: Mfgm Prevents Infection and Improves Gut Barrier Integrity Imentioning
confidence: 71%
“…In a murine model with an early life LPS-induced brain inflammation, the partial replacement of vegetable lipids with dairy lipids had a protective effect on the adverse consequences of LPS exposure on neurogenesis and adult spatial memory (Dinel et al, 2016). In a neonatal piglet model fed IF from birth, the presence of dairy lipids in combination with MGFM changed the dynamic of dairy protein digestion compared to IF containing only vegetable lipids or vegetable lipids plus MFGM, with a higher resistance of casein and b-lactoglobulin to digestion (Le Huërou-Luron et al, 2018). This effect may be related to differences in emulsion interface composition between IFs (Macierzanka et al, 2009).…”
Section: Benefits Of Bovine Milk Fat In Ifsmentioning
confidence: 99%
“…Previous studies have indicated that MFGM significantly impacts on the gut microbiota (Bhinder et al., ; Le Huerou‐Luron et al., ; Thompson et al., ). In this study, MFGM significantly affected relative abundance levels of different bacteria, with the addition of the prebiotic blend further enhancing this impact.…”
Section: Discussionmentioning
confidence: 98%